Learning Development Based On Multicultural In Inclusion School - Abdul Wahid; DYP. Sugiharto; Samsudi Samsudi; Haryono Haryono (FITK UIN Walisongo, 2018)
The aim of the study was to describe the development of multicultural-based inclusion learning in TK Talenta Semarang. This type of research is qualitative descriptive. The findings in this study are that first, multicultural-based inclusion learning is more emphasized in the implementation and evaluation of learning, second, multicultural values grow in students through activities in religious centers that emphasize social piety respecting differences, third: differences in institutions inclusive education is a miniature of diversity in ethnicity, race and religion.AbstrakTujuan penelitian adalah untuk mendeskripsikan pengembangan pembelajaran inklusi berbasis multikultural di TK Talenta Semarang. Jenis penelitian ini adalah deskriptif kualitatif. Temuan dalam penelitian ini adalah bahwa pertama, pembelajaran inklusi berbasis multi kultural lebih ditekankan pada pelaksanaan dan evaluasi pembelajaran, kedua, Nilai-nilai multikultural tumbuh dalam pribadi siswa melalui kegiatan di sentra agama yang menekankan kesalehan sosial menghormati perbedaan, ketiga : perbedaan yang ada di lembaga pendidikan inklusi merupakan miniatur dari keragaman suku, ras dan agama.